Relationship between job satisfaction and employee performance - Issakova, A. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2021)
This study attempts to determine the existence of a relationship between job satisfaction and employee performance and to determine what factors influence employee satisfaction at the large retail company Inditex Kazakhstan. The research was conducted among 50 respondents who are employees of this company. Based on the findings of the study, 3 main factors were identified that largely affect job satisfaction: team, management loyalty and benefits. According to the results of the study, a clear relationship was revealed between high indicators of employee satisfaction with their KPI indicators.
Keywords: job satisfaction, employee performance